2009
DOI: 10.1021/ja809284s
|View full text |Cite
|
Sign up to set email alerts
|

General Synthetic Route to Cell-Permeable Block Copolymers via ROMP

Abstract: The applications of block copolymers are myriad, ranging from electronics to functionalized resins to therapeutics. The ring-opening metathesis polymerization (ROMP) is an especially valuable reaction for block copolymer assembly because each block can be generated with length control. We sought to use this polymerization to expand the repertoire of block copolymers by implementing a strategy that involves post-polymerization modification of a backbone bearing selectively reactive groups. To this end, we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 64 publications
1
106
0
1
Order By: Relevance
“…in solution. In related work, a number of studies with polynorbornenes prepared via ROMP have shown promise for the development of multivalent ligands that can interact with cell surface proteins and be internalized by cells 120,121 , but here we only discuss work with polynorbornenes with polymeric side-chains and other related bottlebrushes.…”
Section: Non-associating Bottlebrushes For Encapsulation and Deliverymentioning
confidence: 99%
“…in solution. In related work, a number of studies with polynorbornenes prepared via ROMP have shown promise for the development of multivalent ligands that can interact with cell surface proteins and be internalized by cells 120,121 , but here we only discuss work with polynorbornenes with polymeric side-chains and other related bottlebrushes.…”
Section: Non-associating Bottlebrushes For Encapsulation and Deliverymentioning
confidence: 99%
“…While functional group placement is limited to one unit at the end of each polymer chain, this approach is complementary to the initiator route so that both ends can be labeled if desired. Alternatively, a reactive group such as activated esters, ketones, or azides can be introduced via the above-mentioned methods which can be then further used to attach dye molecules, an approach which has been quite frequently pursued [3,[76][77][78][79].…”
Section: Functionalization Via the Termination Reagentmentioning
confidence: 99%
“…While activated esters [10,77,81,82] and maleimide functionalities can be straightforwardly (co)polymerized via ROMP, terminal alkynes would participate in a metathesis reaction and therefore need to be protected, typically by a trimethylsilyl group which can be conveniently cleaved after polymerization using tetrabutylammonium fluoride. Azides are also not compatible with ROMP but can be introduced after polymerization by nucleophilic substitution of pendant alkyl halogenide chains [83][84][85].…”
Section: Post-polymerization Modificationmentioning
confidence: 99%
“…The most common method to achieve this aim uses substituted vinyl ethers that already carry the desired end group functionality. [6][7][8][9] Reaction with the propagating ruthenium carbene complex yields a Fischer carbene complex and an end functionalized polymer. Nonetheless, the observed degrees of endfunctionality vary substantially depending on the organic moiety transferred and the E/Z ratio of the vinyl ether substrate.…”
Section: Introductionmentioning
confidence: 99%